Cleidocranial Dysplasia: Management of the Multiple Craniofacial and Skeletal Anomalies. Issue 4 (June 2020) - Jirapinyo, Chutima; Deraje, Vybhav; Huang, Gwendolyn; Gue, Sam; Anderson, Peter J.; Moore, Mark H.
Abstract : Abstract: Cleidocranial dysplasia (CCD) is a rare autosomal dominant disorder caused by mutations in the Runx2 gene. The CCD is characterized by frontal bossing, a patent anterior fontanelle, presence of Wormian bones, midface hypoplasia, multiple dental abnormalities, clavicular hypoplasia or aplasia, skeletal abnormalities, and short stature. The aims of this study are to report the phenotypic manifestations of all patients who presented with CCD and to review the multidisciplinary management of these patients. The longitudinal data of patients with a diagnosis of CCD treated at The Australian Craniofacial Unit from 1980 to 2019 were reviewed. Fourteen patients were identified for inclusion in this study. The age at referral to the unit ranged from 1 week old to 49 years old (mean 11.2 years old). All patients had clinical features of frontal bossing, a patent anterior fontanelle, multiple Wormian bones, midface hypoplasia, abnormal dentition, clavicular hypoplasia/aplasia, and normal intellect. Eleven patients had obstructive sleep apnea. Eight patients had positive family history. Speech issues were found in 6 patients and abnormal hearing was found in 4 patients. Seven patients who underwent skeletal survey were found to have skeletal abnormalities. All patients were evaluated and managed by the multidisciplinary team, which consisted of craniofacial surgeons, pediatric dentists, orthodontists, ENT surgeons, pediatricians, clinical geneticists, radiologists, orthopedic surgeons, and social workers. All patients were treated by dentists/orthodontists requiring multiple surgical interventions and orthodontic treatment. Seven patients who had recurrent ear infection underwent ventilation tube insertion. Seven of 11 patients who had obstructive sleep apnea underwent adenotonsillectomy. Four patients underwent orthognathic surgery to correct midface hypoplasia and malocclusion. Two patients had cranioplasty for correction of metopic depressions. The characteristic findings of patients with CCD involving multiple regions of the body should draw clinicians' attention to the need for multidisciplinary management of these patients. Abstract : Supplemental Digital Content is available in the text